Potential Recovery of Silver (Ag) from X-ray Fixer Waste by Alkaline Treatment - Galarpe, V. R. K. R.; Leopoldo, G. D. (Engineering, Technology & Applied Science Research, 2017)
The study aims to establish a chemical method of silver recovery from x-ray processing fixer waste by alkaline treatment using sodium hydroxide (NaOH). The samples used in the study were collected from selected hospitals and radiology centers in Cagayan de Oro City, Philippines. The NaOH precipitation method was employed by varying the amount of NaOH from 8.00 g to 15.00 g per 600 mL of the fixer waste sample. The recovered crude silver for the two sampling periods ranged from 0.88 g to 2.46 g. The method resulted to optimum recovery at pH 9. The One Way ANOVA indicates that there are significant differences on the amount of silver recovered when varying the amount of NaOH in “sampling A”. The Tukey Test further reveals that there exists an evident rise in the recovered silver using 10.00 g to 15.00 g of NaOH. In “sampling B” the amount of silver recovered does not significantly differ when varying the amount of NaOH used on average basis. The raw data, however, also revealed a significant rise in the amount of silver recovered using 10.00 g to 15.00 g of NaOH where pH was approximately 9.